Self-Reported Halitosis and Associated Factors Among Medical and Dental Students of a Tertiary Institution in Rivers State, Nigeria - Grace Alade; CF Ezebunwa (Nigerian Dental Journal)
Objectives: To determine the prevalence of self-reported halitosis and associated factors among medical and dental students of the university of Port Harcourt.